A deeply divergent lineage of Walkerana (Anura: Ranixalidae) from the Western Ghats of Peninsular India - Dinesh, K.p.; Vijayakumar, S.p.; Ramesh, Vijay; Jayarajan, Aditi; Chandramouli, S.r.; Shanker, Kartik (Zootaxa, 2020)
The frog family Ranixalidae is endemic to the Western Ghats of Peninsular India and contains two genera, Indirana and Walkerana. The three known species of Walkerana are restricted to different hill ranges south of the Palghat Gap, an ancient valley in the Western Ghats. In this study, we report the discovery of a deeply divergent lineage of Walkerana from the high elevations of the Elivalmalai hill range. This finding extends the geographic range of the Walkerana clade to the north of the Palghat Gap. The new species Walkerana muduga sp. nov. is genetically and morphologically divergent, and geographically isolated from its sister lineages. We also recovered a potential new lineage in the adjoining hill ranges suggesting the presence of additional new species in this genus north of the Palghat Gap.